'Aphrodite's Realm': Representations of Tourist Landscapes in Postcolonial Cyprus as Symbols of Modernization. Issue 1 (25th July 2017) - Daskalaki, Georgia
Abstract : The touristic landscape construction and identity politics of Cyprus in the 1960s are manifest in travel guides of the time, after the island's independence from the British, when tourism became a major priority of modernization and nation-building. Through the juxtaposition and interpretation of images depicting tourist landscapes in colonial and postcolonial Cyprus, this paper examines the shift in their construction and representation and explores the gradual transformation of landscape imagery brought about through both the adoption of contemporary international tourist trends and the implementation of contemporary political agendas. These transformed representations of tourist landscapes inevitably suggested new behaviors to be performed in them. Travel guides therefore also played a catalytic role in bringing a modern Mediterranean leisure culture to Cyprus in the 1960s, a culture that was imported and subsequently assimilated by native Cypriot societies in different ways. The aim of this paper is to examine the construction and representation of landscapes and uncover how they can become an instrument for asserting ideologies and shaping identity, especially through the development of tourism.